The “national – local” DIALECTIC in the Tunisian electoral laws or how to represent the “people” in post-Ben Ali Tunisia - Eric Gobe (L’Année du Maghreb)
By exploring the electoral techniques debated by Tunisian political actors, in order to define the conditions of a « good representation » of the « people », this article analyzes the social and political logics underlying the solutions proposed by representatives and rulers of post-Ben Ali Tunisia. Reciprocal relationships between local and national, or more precisely between marginalized regions and the political center, are one of the explanatory factors for the choice of electoral methods made by the rulers of post-Ben Ali Tunisia. The emergence of the « local » in the « national » is translated by the adoption of the first electoral law integrating the issue of the region and by the adoption of a largely decentralized state architecture. The new constitution paved the way for the organization of local collectives directed by elected councils for universal suffrage, and has encouraged actors of the post-Ben Ali political stage to cast a new regard on the effects of electoral methods on the operation of the local as well as national political scene.